Therapeutic potential for peripheral clearance of misfolded brain proteins. Issue 11 (November 2018) - de Leon, Mony; Blennow, Kaj
A new study has shown that peritoneal dialysis and isochronic parabiosis can clear misfolded tau proteins from mouse brain. The findings add to our understanding of how Alzheimer disease-associated proteins can be therapeutically removed by peripheral interventions.